Desain Lanskap Kawasan Stadion Wibawa Mukti berbasis Persepsi Pengguna Stadion - Salma, Jadida; Hadi, Akhmad Arifin (Jurnal Arsitektur Lansekap, 2022)
Landscape d esign of Wibawa Mukti Stadium based on user's perception . High population growth and the development of industrial areas in the Bekasi Regency pose threats to green open space in urban areas. One of the public green open spaces in the Bekasi Regency is the Wibawa Mukti Stadium. Wibawa Mukti Stadium is a sports stadium area that has a function of public green open space. The stadium does not yet have a functional integration between the landscape and buildings in the stadium area. This study aims to produce design works that provide integrated and functional design proposals for the Wibawa Mukti Stadium. The proposed design of this research requires site user perception data that affect the site's sustainability. The research method is qualitative and quantitative methods with data in public perception data related to the ideal sports stadium. Data were taken in social data using interview and questionnaire methods and biophysical data using survey methods. This study's results are in the form of a landscape design of the Wibawa Mukti Stadium area that meets the community's preferences and enhances people's perception of the Wibawa Mukti Stadium. The Wibawa Mukti Stadium landscape can optimally become a green open space for the community by applying the needs of space, facilities, and utilities to the site on the design concept (the concept of space, facilities, and connectedness) according to the needs of the community.